Antibacterial Efficacy of Origanum majorana and Salvia officinalis Extracts Against Escherichia coli and Staphylococcus aureus - Y. Tayeb, Ahmed; Y. Tateb, Anas; Y. Tayeb, Amany (Scientific Journal of University of Benghazi, 2025)
This study evaluated the antibacterial activity of aqueous, ethanol, and essential oil extracts of Origanum majorana and Salvia officinalis against two human pathogens Escherichia coli and Staphylococcus aureus and determined their minimum inhibitory concentrations MICs. The findings indicated that the essential oil extracts were more effective in inhibiting bacterial growth compared to the aqueous and ethanolic extracts. O. majorana essential oil produced the largest inhibition zones: 2.38 cm against Escherichia coli and 2.98 cm against Staphylococcus aureus. Salvia officinalis essential oil showed moderate activity, with inhibition zones of 1.45 cm against E. coli and 1.40 cm against S. aureus. The ethanolic extracts produced limited inhibition (for example, S. officinalis ethanolic extract: 0.57 cm against E. coli; S. officinalis ethanolic extract: 2.17 cm against S. aureus; O. majorana ethanolic extract: 0.45 cm against S. aureus. The aqueous extracts generally exhibited weak activity, except for the O. majorana aqueous extract against E. coli inhibition 2.20 cm and S. officinalis aqueous extract against S. aureus inhibition 1.15 cm. Compared with standard antibiotics tetracycline , chloramphenicol some essential-oil treatments especially marjoram showed comparable activity. The results showed that the essential oils exhibited the strongest antibacterial effect. Among them, O. majorana oil was the most active. Based on these observations, the essential oils of O. majorana and S. officinal might serve as promising natural antibacterial agents and could potentially be applied in combination with standard antibiotics.